Increasing Praise Delivery Within Dorms of a Juvenile Justice Facility. Issue 3 (May 2022) - Luna, Odessa; Rapp, John T.
Researchers have shown that adolescents in residential treatment facilities benefit from behavior-analytic intervention. However, it remains unclear whether practitioners can apply behavioral interventions to increase staff members' appropriate interactions with residents within a juvenile justice facility. In Study 1, researchers compared direct measures of staff behavior in three target dorms (D1, D2, and D3) containing high levels of resident disruptive behavior to a dorm (D4) with consistently low levels of resident disruptive behavior. Results indicated that staff members in the target dorms engaged in significantly higher rates of reprimands and negative statements than in D4. In Study 2, researchers used didactic and video instruction to train staff members in D1, D2, and D3 to increase contingent and noncontingent praise delivery. Results indicated praise delivery by staff members increased slightly in each target dorm. In Study 3, researchers first evaluated the extent to which measures of staff members' and residents' behaviors improved following training within each dorm. Subsequently, researchers compared the post-training behavioral measures from D1, D2 and D3 to D4 to determine the extent to which staff behavior in the training dorms was distinguishable from D4. Results of Study 3 indicated that one or more staff behaviors improved in each training dorm. Nevertheless, residents' disruptive behavior was unchanged in each target dorm. In addition, staff members' behavior in each target dorm continued to be distinguishable from staff members' behavior in D4 on most behavioral measures.